A Single-Chain-Based Hexavalent CD27 Agonist Enhances T Cell Activation and Induces Anti-Tumor Immunity - Thiemann, Meinolf; Richards, David M.; Heinonen, Karl; Kluge, Michael; Marschall, Viola; Merz, Christian; Redondo Müller, Mauricio; Schnyder, Tim; Sefrin, Julian P.; Sykora, Jaromir; Fricke, Harald; Gieffers, Christian; et al. (Frontiers in Oncology, 2018)
Tumor necrosis factor receptor superfamily member 7 (TNFRSF7, CD27), expressed primarily by T cells, and its ligand CD27L (TNFSF7, CD70) provide co-stimulatory signals that boost T cell activation, differentiation and survival. Agonistic stimulation of CD27 is therefore a promising therapeutic concept in immuno-oncology intended to boost and sustain T cell driven anti-tumor responses. Endogenous TNFSF/TNFRSF-based signal transmission is a structurally well-defined event that takes place during cell-to-cell-based contacts. It is well established that the trimeric-trivalent TNFSF-receptor binding domain (TNFSF-RBD) exposed by the conducting cell and the resulting multi-trimer-based receptor clustering on the receiving cell are essential for agonistic signaling. Therefore, we have developed HERA-CD27L, a novel hexavalent TNF receptor agonist (HERA) targeting CD27 and mimicking the natural signaling concept. HERA-CD27L is composed of a trivalent but single-chain CD27L-receptor-binding-domain (scCD27L-RBD) fused to an IgG1 derived silenced Fc-domain serving as dimerization scaffold. The hexavalent agonist significantly boosted antigen-specific T cell responses while having no effect on non-specific T cells and was superior over stabilized recombinant trivalent CD27L. In addition, HERA-CD27L demonstrated potent single-agent anti-tumor efficacy in two different syngeneic tumor models, MC38-CEA and CT26wt. Furthermore, the combination of HERA-CD27L and an anti-PD-1 antibody showed additive anti-tumor effects highlighting the importance of both T cell activation and checkpoint inhibition in anti-tumor immunity. In this manuscript, we describe the development of HERA-CD27L, a true CD27 agonist with a clearly defined forward-signaling mechanism of action.